2023
DOI: 10.1186/s13033-023-00580-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness stigma and associated factors among Arabic-speaking refugee and migrant populations in Australia

Abstract: Background Arabic-speaking refugee and migrant populations form a significant proportion of Australia’s population. Despite high levels of psychological distress among Arabic-speaking populations, low uptake of mental health services has been demonstrated. Evidence suggests poor levels of mental health literacy (MHL) and high levels of stigmatising attitudes among Arabic-speaking populations, which may act as barriers to help-seeking behaviours. This study aimed to explore the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A consistent association between cannabis use and depression was synthesised from the included studies, and, additionally, we observed a higher prevalence of cannabis use among sexual minority groups, including LGBTQI youth, African American youth, and Aboriginal and Torres Strait Islander youth populations [ 5 , 13 , 28 , 37 ]. Such a trend can be explained through the mental health stigma and drug-related stigma in marginalised groups [ 44 , 45 ]. Nevertheless, cannabis use exhibited consistency between male and female youth, with males displaying a higher likelihood of chronic use, while females were more prone to developing adverse mental health outcomes [ 23 , 28 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A consistent association between cannabis use and depression was synthesised from the included studies, and, additionally, we observed a higher prevalence of cannabis use among sexual minority groups, including LGBTQI youth, African American youth, and Aboriginal and Torres Strait Islander youth populations [ 5 , 13 , 28 , 37 ]. Such a trend can be explained through the mental health stigma and drug-related stigma in marginalised groups [ 44 , 45 ]. Nevertheless, cannabis use exhibited consistency between male and female youth, with males displaying a higher likelihood of chronic use, while females were more prone to developing adverse mental health outcomes [ 23 , 28 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed stigma that may contribute to the underdiagnosis of ADHD could have several sources [ 33 , 34 ]. Cultural beliefs and attitudes towards mental health issues are likely to play a significant role, with mental health often being a stigmatized topic in the Arab region [ 35 , 36 ]. It is also important to consider the effect of these cultural attitudes on the family and social networks of individuals.…”
Section: Discussionmentioning
confidence: 99%